Seminario de Posgrado "Discriminación y Violencia de Género: Conceptos, Definiciones, Recolección de Datos y Técnicas de Análisis. Programas de Política Pública en un Mundo Globalizado" (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2023)
This article corresponds to a review of the seminar given by Dr Fiorenza Deriu, from the National University of Rome, from May 23 to June 7, 2023. It was organized by the Interdisciplinary Area of ​​Women's Studies (Department of Social Sciences of the National University of Luján, UNLu), the Interdisciplinary Institute of Women's Studies (Faculty of Human Sciences, National University of La Pampa, UNLPam) and the Interdisciplinary Center for Gender Studies (CIEG, Faculty of Humanities of the National University of Comahue, UNCo), in the latter case, within the framework of the agreement signed by the CIEG and the Minerva Laboratory of the University of Rome "La Sapienza".